A randomized controlled study of intravenous esmolol to attenuate the cardiovascular responses to laryngoscopy and endotracheal intubation - Chodankar, Ninad Deepak; Shivde, Bhagyashree (International Journal of Research in Medical Sciences, 2020)
Background: Objective is to compare the efficacy of intravenous Esmolol to attenuate the cardiovascular responses to laryngoscopy and endotracheal intubation with control group. Methods: Study was done on 60 adults, ASA grade I or II normotensive patients, undergoing elective surgery under general anaesthesia and willing to participate. These patients where be randomly allocated in to either group C (Control) or E (Esmolol). Group ‘C’ Control group. Group ‘E’, patients were given intravenous Esmolol 1.5 mg/kg 2 minutes before start of laryngoscopy. All patients were premedicated, induced and intubated using Thiopentone and Succinyl Choline as per the protocol. Heart Rate (HR), SBP, DBP and MAP were recorded at baseline (taken half an hour prior to anaesthesia), Before sedation, After induction but before intubation, Immediately after endotracheal intubation and Thereafter at 1, 2, 3, 4, 5 and 10 minutes. Results: Heart rate was lower in Group E as compared to Group C, and there was statistically significant difference immediately after intubation till 4 minutes after intubation. While Blood pressure was lower in Group E as compared to Group C, and there was statistically significant difference only immediately after intubation. Conclusions: In Normotensive patients requiring general anaesthesia with laryngoscopy and intubation, authors conclude that intravenous Esmolol 1.5 mg/kg attenuated Heart rate response but fails to satisfactorily prevent rise in blood pressure.